Cryopreservation for the in perpetuity conservation of yam and cassava genetic resources - Dumet, D.; Diebiru, E.; Adeyemi, A.; Akinyemi, O.; Gueye, B.; Franco, J. (2013)
Cryopreservation via droplet vitrification showed high efficiency for cassava meristems (79% average recovery) when these were excised from in vitro seedlings. The efficiency of the process dropped considerably (to >23%) when meristems were excised from field-grown plants, thus precluding the use of such explants for routine cryobanking. In yam, large disparities were observed in the ability of meristems to produce a shoot after cryopreservation ranging from 0 to 60%, depending on the accession. Overall, better recovery was observed for Dioscorea rotundata than for D. alata, the two main species tested. Using a probabilistic decision support tool and taking into consideration our cryoprocessing capacity, we conclude that processing 100 meristems per accession and retrieving 30 to estimate the recovery rate of the batch are a good compromise for the cryobanking routine.